Physical and electromagnetic properties of nanosized Gd substituted Mg–Mn ferrites by solution combustion method - Lwin, N.; Ahmad Fauzi, M.N.; Sreekantan, S.; Othman, R. (Elsevier, 2015)
Nanosized powders of Gd substituted Mg-Mn ferrites synthesized by solution combustion method using high purity metal nitrates are presented. These powders were calcined, compacted and sintered at 1250 degrees C. The powders were characterized by X-ray powder diffraction (XRD) and transmission electron microscopy (TEM). The effect of Gd substitution on phase formation, microstructure and bulk density was also studied. Gd2O3 facilitates the formation of a secondary phase on the grain boundary which suppresses abnormal grain growth. The bulk density was found to decrease from 426 to 3.38 g/cm(3) with an increase of Gd substitution, but the electrical resistivity was increased. Ferrite with a low dielectric constant in the range of 6-12 was observed and there was no maximum dielectric loss in the frequency range measured to 1 GHz. A decrease in saturation magnetization was also observed by a small fraction of Gd substitution. Correlation between magnetic properties and physical properties were discussed. (C) 2015 Elsevier B.V. All rights reserved.